2020
DOI: 10.1136/bmjoq-2019-000749
|View full text |Cite
|
Sign up to set email alerts
|

Doing our work better, together: a relationship-based approach to defining the quality improvement agenda in trauma care

Abstract: BackgroundTrauma care represents a complex patient journey, requiring multidisciplinary coordinated care. Team members are human, and as such, how they feel about their colleagues and their work affects performance. The challenge for health service leaders is enabling culture that supports high levels of collaboration, co-operation and coordination across diverse groups. We aimed to define and improve relational aspects of trauma care at Gold Coast University Hospital.MethodsWe conducted a mixed-methods collab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…While studies of relational interventions are in their infancy compared with studies of structural interventions, nearly all reported findings have been positive. Relational interventions have been associated with increased relational coordination (e.g., Abu-Rish Blakeney et al, 2019;Brazil et al, 2019;Cramm & Nieboer, 2014b;Purdy et al, 2020;Ross, 2015), as well as increased efficiency (Bitter, 2017), and improved quality (Goldstein et al, 2014) in the health care sector. Often these relational interventions have been implemented in tandem with structural interventions such as cross-functional training programs (Ross, 2015) and cross-functional meeting structures (Abu-Rish Blakeney et al, 2019).…”
Section: Relational and Work Process Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies of relational interventions are in their infancy compared with studies of structural interventions, nearly all reported findings have been positive. Relational interventions have been associated with increased relational coordination (e.g., Abu-Rish Blakeney et al, 2019;Brazil et al, 2019;Cramm & Nieboer, 2014b;Purdy et al, 2020;Ross, 2015), as well as increased efficiency (Bitter, 2017), and improved quality (Goldstein et al, 2014) in the health care sector. Often these relational interventions have been implemented in tandem with structural interventions such as cross-functional training programs (Ross, 2015) and cross-functional meeting structures (Abu-Rish Blakeney et al, 2019).…”
Section: Relational and Work Process Interventionsmentioning
confidence: 99%
“…How can change agents help organizations learn how to coordinate? As shown above, change agents can engage in relational interventions such as humble inquiry and empathetic connection to establish a safe space to reflect on interdependencies and transform fragmented relationshps into more connected ones (Abu-Rish Blakeney et al, 2019;Gittell, 2016;Purdy et al, 2020). As relational coordination begins to gain strength, change agents are able to implement structural interventions with relational intent, thus further reinforcing relational coordination.…”
Section: Helping Organizations Learn How To Coordinatementioning
confidence: 99%
“…Recently, we undertook a study of relational coordination and the culture of trauma care at Gold Coast University Hospital, a large tertiary care and trauma centre in Australia. 10 Data was collected using a quantitative relational coordination survey in conjunction with an ethnography-participant observation, interviews, and working groups-with the trauma service. The study was approved by the Gold Coast University Hospital ethics review board (HREC/18/QGC/13).…”
Section: Macro Relational Coordination In Traumamentioning
confidence: 99%
“…Given our existing relationships with clinical services, our focus was on team and system challenges. We felt that our specific expertise in building relationships and shaping culture through simulation [7,8] was likely to be more important than ever as we undertook rapid and urgent high stakes change. Our strategy was aligned with the Queensland Health Pandemic Influenza Plan [9] and guided by the local Health Emergency Operations Centre (HEOC), to whom we provided biweekly reports.…”
Section: Our Strategy Developmentmentioning
confidence: 99%